Non-volatile electrical polarization switching via domain wall release in 3R-MoS2 bilayer - Dongyang Yang; Jing Liang; Jingda Wu; Yunhuan Xiao; Jerry I. Dadap; Kenji Watanabe; Takashi Taniguchi; Ziliang Ye (Nature Communications, 2024)
Abstract Understanding the nature of sliding ferroelectricity is of fundamental importance for the discovery and application of two-dimensional ferroelectric materials. In this work, we investigate the phenomenon of switchable polarization in a bilayer MoS2 with natural rhombohedral stacking, where the spontaneous polarization is coupled with excitonic effects through asymmetric interlayer coupling. Using optical spectroscopy and imaging techniques, we observe how a released domain wall switches the polarization of a large single domain. Our results highlight the importance of domain walls in the polarization switching of non-twisted rhombohedral transition metal dichalcogenides and open new opportunities for the non-volatile control of their optical response.